Intramolecular azide-alkene cycloaddition-elimination reaction in an aldohex-2-enonic acid derivative. (1st September 2019) - Repetto, Evangelina; Oliveira Udry, Guillermo A.; Varela, Oscar
Abstract: A 6-azido-2-tosylenolate, obtained from D-glucono-1, 5-lactone in six steps, underwent an intramolecular cycloaddition–elimination pathway under mild conditions, yielding a chiral, substituted 5, 6-dihydro-4 H -pyrrolo[1, 2- c ]-1, 2, 3-triazole. The conditions were optimized to give exclusive formation of the triazole. The mechanism appears to involve intramolecular ring closure via a 1, 3-dipolar azide–alkene cycloaddition to give a 1, 2, 3-triazoline, followed by elimination of p -toluenesulfonic acid, leading to aromatization. Triazole products, obtained by chemical modification, are expected to display activity as enzyme inhibitors. Furthermore, partially protected derivatives of the 2-hexenoate were prepared as useful synthetic intermediates. Graphical abstract: Image 1 Highlights: Synthesis of a key intermediate methyl 2-hexenoate fromd -gluconolactone. Reaction of the 2, 6-di- O -tosylhexenoate with azide gave a bicyclic triazole. An intramolecular azide-alkene cycloaddition-elimination mechanism is proposed. The bicyclic triazole and derivatives are potential enzyme inhibitors. Derivatives prepared from the key 2-hexenoate are useful synthetic precursors.